Statistical association of rs2243250 polymorphism of IL4 gene and hemorrhagic stroke in Brazilian population - Ângelo M. Rolim; Felipe S. A. Borges; Aline R. Barros; Jonathan D. Lima; Fabiana B. A. Silva; Hélia Carla de Souza; Daniel O. Freire; Luzitano B. Ferreira; Izabel Cristina R. Silva
ABSTRACT Interleukin-4 (IL-4) has great significance in inflammatory processes in cases of stroke, since it is able to polarize microglia to the antiinflammatory phenotype called M2. This study analyzed if the variation between TT genotype and the other genotypes (CT and CC), in -589 (rs2243250) polymorphism of IL4 gene, has association with the prognosis of hemorrhagic stroke (HS) and with clinical aspects which are risk factors for cerebrovascular diseases. The result of this study shows that there is no statistical association of the IL4 polymorphism with either prognosis or clinical aspects in HS patients.